Nontarget-Site Resistance to ALS Inhibitors in Waterhemp (Amaranthus tuberculatus). Issue 2 (June 2015) - Guo, Jiaqi; Riggins, Chance W.; Hausman, Nicholas E.; Hager, Aaron G.; Riechers, Dean E.; Davis, Adam S.; Tranel, Patrick J.
Abstract : A waterhemp population (MCR) previously characterized as resistant to 4-hydroxyphenylpyruvate dioxygenase and photosystem II inhibitors demonstrated both moderate and high levels of resistance to acetolactate synthase (ALS) inhibitors. Plants from the MCR population exhibiting high resistance to ALS inhibitors contained the commonly found Trp574Leu ALS amino acid substitution, whereas plants with only moderate resistance did not have this substitution. A subpopulation (JG11) was derived from the MCR population in which the moderate-resistance trait was isolated from the Trp574Leu mutation. Results from DNA sequencing and ALS enzyme assays demonstrated that resistance to ALS inhibitors in the JG11 population was not due to an altered site of action. This nontarget-site ALS-inhibitor resistance was characterized with whole-plant dose–response experiments using herbicides from each of the five commercialized families of ALS-inhibiting herbicides. Resistance ratios ranging from 3 to 90 were obtained from the seven herbicides evaluated. Nontarget-site resistance to ALS has been rarely documented in eudicot weeds, and adds to the growing list of resistance traits evolved in waterhemp.